Recipes and cookbooks for the national pot: The construction of the Colombian culinary project in the nineteenth century (2014)
During the XIX century, the nation-building project in Colombia conceived by the literate elites, considered issues such as the country's political and geographical organization, the establishment of a stable economy, and the formation of a republican government. This project, conceived by a male leadership also included a reflection on cultural topics and daily habits. As a result, between 1830 and 1882, spaces of women's domestic practices and interactions, like the kitchen, were influenced by the elite's ideological tendencies through the development of culinary publications. The present paper will discuss how culinary literature and recipes inspired by women's domestic knowledge were employed in the construction of Colombian national identity in the nineteenth century.